Citizenship Status, Statehood Problems and Political Conflict: The Case of Nigeria (Nordic Journal of African Studies, 2000)
Perhaps the most enduring, even if not the most accurate, image of Africa in the seventies, eighties and nineties has been that of a continent of violence perennially on the edge of survival... Africa thus stands singled out as a continent of uniquely violent politics, a continent where force makes the everyday life of the people even more demeaning than in other poor parts of the world.